U.S. Foreign Policy in the Middle East: Strategic Goals, Oil Interests, and the Promotion of Democracy - Zazai, Abuzar Khpalwak; Jamili, Fawad (PT. Riset Press International, 2025)
This research explores the historical and contemporary role of U.S. intervention in the Middle East, with a particular focus on oil interests, political strategies, and regional stability. The study examines key agreements like the